2021
DOI: 10.1155/2021/6641031
|View full text |Cite
|
Sign up to set email alerts
|

Targeting miRNA by Natural Products: A Novel Therapeutic Approach for Nonalcoholic Fatty Liver

Abstract: The increasing prevalence of nonalcoholic fatty liver disease (NAFLD) as multifactorial chronic liver disease and the lack of a specific treatment have begun a new era in its treatment using gene expression changes and microRNAs. This study aimed to investigate the potential therapeutic effects of natural compounds in NAFLD by regulating miRNA expression. MicroRNAs play essential roles in regulating the cell’s biological processes, such as apoptosis, migration, lipid metabolism, insulin resistance, and adipocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 158 publications
0
17
0
1
Order By: Relevance
“…Thus, a possible mechanism is that the increased lipid sequestration in lipid droplets results in insufficient membrane permeability to allow virion formation, resulting in decreased virus production, and increased cellular E protein, as observed in this study. However, berberine has been shown to act through a number of other mechanisms including acting as an antioxidant and anti-inflammatory [57], as a repressor of DNA repair and replication [58], modulating noncoding RNAs, including miRNAs [59] and modulating autophagy [60], all of which could possibly impact how berberine affects viral replication, or its effects in other disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a possible mechanism is that the increased lipid sequestration in lipid droplets results in insufficient membrane permeability to allow virion formation, resulting in decreased virus production, and increased cellular E protein, as observed in this study. However, berberine has been shown to act through a number of other mechanisms including acting as an antioxidant and anti-inflammatory [57], as a repressor of DNA repair and replication [58], modulating noncoding RNAs, including miRNAs [59] and modulating autophagy [60], all of which could possibly impact how berberine affects viral replication, or its effects in other disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, differentiation-promoting drugs may be able to delay the growth of GBM and medulloblastoma in patients, diminish cancer resistance, and avoid recurrence [ 99 ], as evidenced by decreased nesting (a stem cell marker) and increased expression of the glial acidic fibrillary protein (a mature glial cell marker) and beta III-tubulin (a neuronal differentiation marker) in human U87MG cells over time. Numerous investigations have demonstrated that RES has anticancer properties at the level of posttranscriptional gene expression regulation [ 127 ]. Thrombotic Thrombocytopenic Purpura (TTP) is an RNA binding protein that binds to AU-rich regions in target mRNAs and promotes the deadenylating and destruction of target transcripts, including proto-oncogenes, antiapoptotic genes, immune regulatory genes, and others.…”
Section: Control Of Cellular Proliferation Apoptosis and Differentiationmentioning
confidence: 99%
“…MicroRNAs (miRNAs) play important roles in regulating cell apoptosis, migration, and lipid metabolism during the development of NAFLD [ 108 ], which may function as diagnosis markers (e.g., miR-144-3p and miR-200b-3p) [ 109 ]. Keeping the balance of Th17/Treg ratio via modulating miR-195 expression can inhibit CD40 expression to ameliorate NAFLD in rats.…”
Section: Treatment Options For Nafld and Nash Based On Modulation Of Gut Microbiota Intrahepatic Immunity And Metabolic Signaling Pathwaymentioning
confidence: 99%